Native welfare losses from high skilled immigration - Alexander Kemnitz (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper explores the effects of high skilled immigration to a host country with unionized low skilled labor and an unemployment insurance scheme. We show that such immigration can create a negative immigration surplus due to adverse effects on low skilled employment, provided that fiscal redistribution is not too intense and the elasticity between high and low skilled labor is high as empirical evidence suggests.
Keywords: F22; J5; H53; J61; J65; 330; Immigration; trade union; unemployment; welfare state; elasticity of substitution; Hochqualifizierte Arbeitskräfte; Einwanderung; Wohlfahrtseffekt; Ungelernte Arbeitskräfte; Gewerkschaftlicher Organisationsgrad; Substitutionselastizität; Arbeitslosigkeit; Theorie